A preliminary checklist of Chironomidae (Diptera) from Albania with first records for the Balkan Peninsula - Bitušík, Peter; Trnková, Katarína (Zootaxa, 2019)
The Chironomidae of Albania have so far received limited attention and only 39 species have been recorded prior to the present study. Here we bring the results of random and non-intensive samplings of chironomid pupal exuviae and adults, at five localities in 2012, that provided 55 species and 5 additional taxa, with 51 being new for the Albanian fauna, out of which 7 were new for the Balkan Peninsula. In addition to that, we present a preliminary checklist of Chironomidae based on the data from Fauna Europaea complemented by the results of the recent investigation. The catalogued fauna now contains 85 species in 44 genera and 6 sub-families.